Training of Simple Financial Accounting in Bengkel DIFA SMALB D/D1 YPAC Surakarta - Dewita Puspawati; Novel Idris Abas; Muhammad Wahyuddin (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The development of entrepreneurship programs is very much needed for children with special needs. This is due to increase the independence of students, especially after graduating from school. In support of this, the UMS community service team conducted a community service program at SLB-D YPAC Surakarta. This community service program is to help children with special needs understand and make financial reports for the skills business unit at SLB-D YPAC Surakarta, especially the DIFA motorcycle wash program. The form of this community service program is counseling and training which is divided into two parts. The first part is about learning simple financial statement bookkeeping which is followed by all students of SMA SLB-D YPAC Surakart. The second part is about the practice of making financial reports with the object of which is a skills business unit which is followed by a team that is directly involved in the SLB-D YPAC Surakarta skills unit. The output of this community service program is that the training participants have a better understanding of accounting for financial reports and how to make them and have a reference to financial reports for the skills business unit at SLB-D YPAC Surakarta.